Legal Protection for Consumers Who Are Injured Due to Mechanic Negligence in Repairing Motorcycles - Anhar, Romy Ashadin; Mardijono, HR Adianto (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2024)
Sometimes accidents are not always due to the negligence of the motorbike driver, but are caused by the unfitness of the vehicle which is caused by the motorbike mechanic being negligent in providing motorbike repair services to motorbike users. Even though accidents often occur due to unsuitable motorbike spare parts, until now there has been no protection for consumers who are injured because mechanics are negligent in providing their services. Therefore, consumer protection is needed for mechanical services that are negligent in providing their services, resulting in harm to the consumer. In this research, the author uses method,a normative juridical with the approach of statutory regulatory approach and a conceptual approach. The purpose research is to find out how legal protection is for consumers,who are injured due to mechanic negligence in repairing motorbikes. As for the results of this research, a vehicle being repaired in a motorbike repair shop experienced an accident due to mechanical negligence, the business actor can be considered as the business actor who is responsible for the accident, following the principle of liability based on fault which is used in general consumer protection law.